The Relationship of Online Game Addiction Level Towards Prayer Behavior in Adolescents - Jamilatun Fajar; Mamnuah Mamnuah (International Journal of Health Science and Technology, 2022)
Excessively playing online games will create a strong addiction in a person. Indonesia first rank in the largest number of game players in Southeast Asia, both those who play games on smartphones, personal computers, and laptops. A person's inability to control the use of social media and online gaming via gadgets will cause them to lose their track of time, including the time to pray. This research aims to discover the relationship of online game addiction level towards the prayer behavior on adolescents. This research was conducted through observational quantitative with correlation research design and used cross sectional approach. The respondents were 128 students gathered through simple random sampling technique. The instruments were questionnaire and Kendall Tau data analysis. There is no relationship between online game addiction level with prayer behavior level on adolescents (p-value 0.915 0.05). Adolescents' discipline in carrying out prayers, both in terms of the timeliness of prayer and the completeness of the five daily prayers, is still lacking.